The model professionalism in the implementation of the Nursing Process (1979-2004) - Silvana Alves Benedet; Maria Itayra Padilha; Francine Lima Gelbke; Maria Ligia dos Reis Bellaguarda
ABSTRACT Objective: to assess the contribution of the introduction and implementation of the Nursing Process of the University Hospital of the Federal University of Santa Catarina (Universidade Federal de Santa Catarina - UFSC) for the progress of the profession from 1979 to 2004. Method: qualitative and social-historical study. We used oral and documentary sources for data collection, through semi-structured interviews with 14 nurses and documentary analysis. The study was analyzed under Eliot Freidson theory of content and theoretical reference, on the sociology of professions. Results: the challenges mentioned were lack of knowledge; nurses overloaded with responsibilities; precarious physical space and materials; lack of consideration of the Nursing Process by the multiprofessional team. The political participation of the professors of the Nursing Department was fundamental for the successful introduction of the Nursing Process. We emphasize the professional commitment of nurses to face the challenges presented. Conclusion: the introduction and implementation of the Nursing Process contributed to the progress of nursing in the state of Santa Catarina regarding appreciation and professionalization.